Increased Responsiveness of Human Coronary Artery Endothelial Cells in Inflammation and Coagulation - Katja Lakota; Katjusa Mrak-Poljsak; Blaz Rozman; Snezna Sodin-Semrl (Mediators of Inflammation)
The effects of anti-inflammatory plant extracts, such as black tea extract (BTE) and resveratrol (RSV) could modulate cell activation leading to atherosclerosis, however there is little comparative information about how different endothelial cell types are affected by these compounds. In order to compare human endothelial cells derived from different origins (umbilical vein or HUVEC, coronary artery or HCAEC, microvascular or HMVEC) and their interleukin-1β (IL-1β) responsiveness, IL-6 ELISA, RT-PCR, tissue factor assay, and prostacyclin responses using 6-keto PGF1α ELISA were determined. The IL-1β-induced IL-6 levels were dose-dependent with highest responses seen in HCAEC. Significant inhibition of IL-1β responses was achieved with BTE and RSV, with the largest decrease of IL-6 and TF seen in HCAEC. Prostacyclin levels were highest in HUVEC and were inhibited by RSV in all cell types. The differences between the endothelial cell types could account for greater susceptibility of coronary arteries to inflammation and atherogenesis.